2016
DOI: 10.1142/s0217732316400058
|View full text |Cite
|
Sign up to set email alerts
|

Massive gauge-flation

Abstract: Gauge-flation model at zeroth order in cosmological perturbation theory offers an interesting scenario for realizing inflation within a particle physics context, allowing us to investigate interesting possible connections between inflation and the subsequent evolution of the Universe. Difficulties, however, arise at the perturbative level, thus motivating a modification of the original model. In order to agree with the latest Planck observations, we modify the model such that the new dynamics can produce a rel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 34 publications
(40 reference statements)
1
45
1
Order By: Relevance
“…while the latter are given by 2 [7,8] [15] Higgsed 0 1 L Gf [12,16] L Cn [14] Spectator-Higgsed 1 1 L Gf − L Cn − Table 1. Inflationary models involving an SU (2) gauge field in the literature and their relation to L A , α s and α H .…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…while the latter are given by 2 [7,8] [15] Higgsed 0 1 L Gf [12,16] L Cn [14] Spectator-Higgsed 1 1 L Gf − L Cn − Table 1. Inflationary models involving an SU (2) gauge field in the literature and their relation to L A , α s and α H .…”
Section: )mentioning
confidence: 99%
“…On the other hand, J A should be at most on the order of the slow-roll suppressed terms, i.e., J A H 2 ψ ≡ B A 1, which is more restrictive. Before we leave this section, let us comment on the Higgsed models, e.g., Higgsed gauge-flation and Higgsed chromo-natural models [12,14,16]. Both scalar and tensor perturbations are amplified by the Higgs VEV in this set up, with the scalar ones being more strongly amplified; thus, the Higgs VEV, quantified by ξ Z 0 , reduces the tensor-toscalar ratio [14,16].…”
Section: Parameter Space Of Massless Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, it has been recently shown that this mechanism does not generate a sufficient lepton asymmetry without spoiling inflation [28]. Other, more promising examples are inflationary scenarios that contain SU(2) gauge fields with classical vacuum expectation values, such as gauge-flation [29][30][31] and its variants [32,33], chromo-natural inflation (CNI) [34][35][36][37] and its variants [38][39][40], and models that include spectator chromo-natural-like sectors [41][42][43][44]. Gravitational leptogenesis has been studied within the context of these SU(2) models [45][46][47]; however, these works focused on the UV modes and suffer from similar criticisms regarding regularization and renormalization as the original proposal.…”
Section: Gravitational Leptogenesismentioning
confidence: 99%
“…[33][34][35] as extensions of the original Chromo-natural model. Within the framework of gaugeflation, it remains to be explored whether more general Lagrangians can be compatible with observations, e.g., its massive variant [36].…”
Section: Introductionmentioning
confidence: 99%